2016
DOI: 10.1136/bmjopen-2015-010158
|View full text |Cite|
|
Sign up to set email alerts
|

Cluster randomised controlled trial of a financial incentive for mothers to improve breast feeding in areas with low breastfeeding rates: the NOSH study protocol

Abstract: IntroductionBreast feeding can promote positive long-term and short-term health outcomes in infant and mother. The UK has one of the lowest breastfeeding rates (duration and exclusivity) in the world, resulting in preventable morbidities and associated healthcare costs. Breastfeeding rates are also socially patterned, thereby potentially contributing to health inequalities. Financial incentives have been shown to have a positive effect on health behaviours in previously published studies.Methods and analysisBa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…This is the first study of women’s experiences of being offered a financial incentive to breastfeed. It was conducted alongside a large cluster randomised controlled trial of the financial incentive (details [ 11 ] and findings [ 12 ] are published elsewhere) to explore acceptability of the scheme in practice and to contextualise the trial findings [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study of women’s experiences of being offered a financial incentive to breastfeed. It was conducted alongside a large cluster randomised controlled trial of the financial incentive (details [ 11 ] and findings [ 12 ] are published elsewhere) to explore acceptability of the scheme in practice and to contextualise the trial findings [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Responses from the first stage (development) were used to inform the study design [ 9 ] which was tested in the second (feasibility) stage [ 10 ]. The purpose of this paper is to help interpret the results of the full trial (details [ 11 ] and findings [ 12 ] are published elsewhere). The trial reported a significant increase in breastfeeding at 6–8 weeks for those clusters where the NOSH Scheme was offered [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While data unavailability precluded estimating effectiveness at 6 months, total costs of vouchers were included in the analysis because the offer of vouchers up to 6 months was provided to participants at the outset of the trial and could therefore had impacted on the take up and duration of breast feeding. The protocol planned cost-effectiveness analysis10 was published prior to the analysis. The Trial Steering Committee approved changes from protocol to analyses.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome this perception, U.K. researchers have developed and trialled financial incentives for breastfeeding, in the form of shopping vouchers worth up to £200 in total (Relton et al, ). Results suggest that areas with low breastfeeding rates that offer financial incentives have significantly increased breastfeeding rates at 6–8 weeks post‐natal age (Relton et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Results suggest that areas with low breastfeeding rates that offer financial incentives have significantly increased breastfeeding rates at 6–8 weeks post‐natal age (Relton et al, ). Financial incentives were provided, on the basis of self‐report of breastfeeding corroborated by a confirmatory signature from an appropriate health care worker (Relton et al, ). This is the method by which infant feeding status is recorded for the purposes of routine data collection in the U.K.'s National Health Service: a healthcare professional's determination based on their interactions with the woman during routine visits (which may or may not include witnessing the woman breastfeed).…”
Section: Introductionmentioning
confidence: 99%